Genomic Approaches to Understanding Asthma - Palmer, Lyle J.; Cookson, William O.C.M. (Genome Research, 2000)
Asthma is the most common chronic childhood disease in developed nations, and it is a complex disease that has high social and economic costs. Asthma and its associated intermediate phenotypes are under a substantial degree of genetic control. The genetic aetiology of asthma offers a means of better understanding its pathogenesis and, thus, improving preventive strategies, diagnostic tools, and therapies. Considerable effort and expense have been expended in attempts to detect genetic loci contributing to asthma susceptibility, and extensive candidate gene studies and a number of whole-genome screens have been undertaken. This article reviews the current state of knowledge of the genetics of asthma, with a focus on genomic approaches to understanding allergic diseases.
10.1101/gr.143400